The Development Of The Song “Jangan Kawin Muda” For Postpone Of Early Marriage In Adolescent (Universitas Negeri Semarang, 2022)
Early marriage is one of the problems faced by the Indonesian people, because it has a negative impact on the increase in the divorce rate for young couples. Furthermore, divorce will suffer children, because they do not get the attention and love of their parents, so they become neglected children. One of the causes of early marriage is the lack of information about the bad effects of early marriage. On this basis, this research is a development of previous research (Dariyo, Rahaditya & Hadiati, 2020) with the aim of providing information about the dangers of early marriage, which is realized with the song